Long-term contracts for network-supportive flexibility in local flexibility markets - Erik Heilmann; Nikolai Klempp; Kai Hufendiek; Heike Wetzel (Philipps-University Marburg, School of Business and Economics, 2022)
With an ongoing energy transition, the electric network is increasingly challenged. Handling congestion is a major responsibility of network operators. In recent years, market-based approaches to utilize network-supportive exibility, especially local exibility markets (LFMs), have been discussed as possible future development of congestion management processes. LFMs are a promising opportunity for the efficient, transparent and non-discriminatory integration of new exibility options, in particular demand-side exibility. Despite a wide body of supporting literature and several pilot implementations, there is still no common commitment to the concept of LFMs in the European Union. Here we address decision makers in the European energy economy, especially network operators, and discuss a possible exibility product design using a methodological approach with four steps. First, we review the theoretical background of LFMs, considering both network operators' views and the possibility of demand response as a exibility provider. Based on this review, we formulate an interim conclusion regarding requirements for exibility product design in general. Second, using an existing framework, we propose a concrete, capacity-based, long-term exibility product specification. Third, we discuss compliance between the defined requirements and the proposed product design to highlight the relevance of key design parameters and identify further research needs. Finally, we derive policy implications for network operators' decision makers regarding the implementation of LFMs.
Keywords: D47; L94; Q41; 330; demand side flexibility; local flexibility market; congestion management; flexibility product design